Ultrastructure of the ovary of Dermatobia hominis (Diptera: Cuterebridae): III. Gonial cell degeneration - Secco, V. N. D. P. [UNESP]; Gregorio, E. A. [UNESP]; Toledo, L. A. [UNESP]; Lello, E. [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1992)
We studied the ultrastructural aspects of pre-pupae and pupae ovaries of Dermatobia hominis. Physiological degeneration of gonial cells was observed: (a) after the ovarioles differentiation, in the oogonia residing in the apical region of the ovary; (b) at the beginning of vitellogenesis, in the cystoblasts close to the terminal filament. The significance of gonial cell degeneration was correlated with the physiological changes wich occur in the ovary during development.
Keywords: ovary; bot-fly; Diptera; gonial cell; Dermatobia hominis